2009
DOI: 10.1164/rccm.200805-669oc
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Intervention with Weight Reduction

Abstract: VLCD combined with active lifestyle counseling resulting in marked weight reduction is a feasible and effective treatment for the majority of patients with mild OSA, and the achieved beneficial outcomes are maintained at 1-year follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
92
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 354 publications
(102 citation statements)
references
References 44 publications
5
92
0
5
Order By: Relevance
“…Weight loss is strongly recommended for patients with obesity related diseases such as obstructive sleep apnea [51], [52], but the effect of early intervention on lung and cardiac function in asymptomatic obese subjects is less clear. It has previously been shown that surgical induced weight loss has positive effects on cardiac function [31], [53], [54], [55], [56].…”
Section: Discussionmentioning
confidence: 99%
“…Weight loss is strongly recommended for patients with obesity related diseases such as obstructive sleep apnea [51], [52], but the effect of early intervention on lung and cardiac function in asymptomatic obese subjects is less clear. It has previously been shown that surgical induced weight loss has positive effects on cardiac function [31], [53], [54], [55], [56].…”
Section: Discussionmentioning
confidence: 99%
“…Although bariatric surgery leads to a greater weight loss at 1 year, intensive lifestyle interventions similar to that employed here lead to clinically significant weight loss and similar improvements in risk factors and resolution of comorbidities in patients with morbid obesity [23] . Randomized controlled trials strongly suggest that weight reduction from a healthy diet and increased physical activity may correct or at least improve symptoms in patients with mild OSA and in OSA patients with diabetes [12,24] .…”
Section: Discussionmentioning
confidence: 99%
“…Because of her morbid obesity, severe OSA and family history of cardiac disorders, we decided to put this patient on a VLCD as previously used safely and efficiently for the treatment of OSA [12,13] and in the long-term (i.e., > 12-month) treatment of severe obesity [17] . Furthermore, a review of randomized controlled trials has reported that VLCD with active follow-up treatment seems to be one of the better treatment modalities related to long-term weight-maintenance success [18] .…”
Section: Case Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies, both large population-based and clinical, have concretely established relationships between obstructive sleep apnoea, type 2 diabetes, and obesity. [8][9][10][11] As the obesity epidemic continues, the prevalence of OSA and type 2 diabetes will increase. Many patients with type 2 diabetes have OSA, but unfortunately majority of them are unaware of it and remain undiagnosed.…”
Section: Introductionmentioning
confidence: 99%